Innovations spearheading the next transformations in India's agriculture - Kavery Ganguly; Ashok Gulati; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2017)
Innovations are fast changing the agricultural landscape driven by the increasing need to shift towards sustainable practices without sacrificing the productivity and profitability of farming. Innovations in technology, institutions, processes, and products have contributed to the growth of agriculture, globally and in developing countries including India and Africa, as observed in the cases of green revolution in cereals; and gene revolution in cotton. More recently, innovations in farm mechanization, micro irrigation, digital technology driven farm and crop management, financial services, energy efficient post-harvest management including LED and solar driven logistics, among others are gaining momentum. These have considerable potential to impact farmers' livelihood through higher productivity, better returns, more employability and in turn catalysing the shift towards sustainable agricultural practices through optimal utilization of resources. In addition to these, innovations in business models - "uberization" of agri-mechanization, direct firm-farm linkages, aggregation of farmers through producer organizations, etc. that make agricultural technology more affordable and adoptable for smallholder farmers are critical for economic and human development of people who depend on agriculture for their income and livelihood security and in effect impact poverty alleviation. For the developing world, innovations must infuse inclusive growth and deliver maximum benefits to the smallholder farmers. The present study involves an extensive stocktaking exercise of the types of innovations that have emerged globally and in India in particular, and their increasing impact on the agricultural sector. The stocktaking exercise is based not only on peer-reviewed research from the academic fields, but also draws on recent corporate studies. This is done because we observe an accelerated innovation process in which business and startups (for instance in digital services) play an important role. The important trends and therein the lessons learnt which can be adapted to suit the local conditions in India are captured. The study also looks into the policy and institutional reforms that will catalyze the introduction and adoption of the advanced technology solutions in the context of Indian agriculture.
Keywords: O32; Q 13; Q15; Q16; 330; Innovations; agribusiness; irrigation; agricultural technology